Analisis Pengaruh Persepsi dan Sikap Keselamatan dan Kesehatan Kerja (K3) terhadap Perilaku Keselamatan dalam Perawatan Sarana KA - Ajeng Tyas Damayanti (Journal on Education, 2023)
The use of machinery, electrification and modernization of various means of production are absolute in the current era of globalization. This has an impact on business owners as well as human resources. One of them is the existence of work risks that arise. It is important for companies to ensure that their employees have OSH perceptions and attitudes that are in accordance with safety behavior in the workplace. This study aims to determine the effect of OSH perceptions and attitudes on safety behavior in the maintenance of railway facilities. This research was conducted by giving questionnaires in the form of a Likert scale to respondents. The results of the data analysis show that there is an influence of OSH perceptions on safety behavior as evidenced by the descriptive variable of 89,4 and this OSH perception has a greater influence than OSH attitude. The linear regression result is 0.263. The t test result is 2.372 with a significance of 0.031. The influence of OSH attitudes on safety behavior is evidenced by a descriptive variable of 85.1. The results of linear regression showed a result of 0.337 and t test 3.568 with a significance of 0.001.